The assemblages with bifacial pieces during Lower and Early Middle Pleistocene in East Africa and Near East. New approach of the bifacial phenomenon applied to the issues of migrations, diffusion and local evolution. - (:unkn) unknown (My University, 2012)
The “Out of Africa” model is deeply rooted in the issues of Paleolithic settlement. For the Lower and Early Middle Pleistocene, several waves of early hominid dispersal from Africa have been proposed, especially to the Near East on the basis of three major sites: Dmanisi, 'Ubeidiya and Gesher Benot Ya'aqov. This theory also conveys the idea of repeated imports of new techniques, including bifacial shaping.However, the mechanisms inherent in this model are deconstructed: it allows to identify conceptual and methodological obstacles from the “arrow paradigm”, which simplifies and reduces the complexity of technical and cultural phenomena.The absence of space and time in the “Out of Africa” model is a crippling flaw. To reintroduce these dimensions in the debate, an evolutionary view of technics is used and is inspired by thoughts from philosophy, ergonomics and geography. In Paleolithic prehistory, this point of view, developed over past fifteen years, led to work out a techno-functional methodology focused on notions of tool, gesture and functioning.A detailed study using this approach was conducted on four assemblages from East Africa and Near East, with some supplementary observations on three other collections Then a discussion is offered on various topics: (1) the processes of technical evolution over long time, (2) an alternative vision of settlements, which particularly considers the idea of independent inventions of bifacial shaping, and finally (3) the ability to define cultural spaces on different scales of time and space.
Keywords: African Research